Knowledge productivity for sustainable innovation: social capital as HRD target. Issue 1 (6th January 2014) - Ehlen, Corry; Van der Klink, Marcel; Roentgen, Uta; Curfs, Emile; Boshuizen, Henny
Abstract : Purpose: – The purpose of this paper is to test the feasibility of a conceptual model on relations between organisational innovation, knowledge productivity and social capital. It explores processes of knowledge productivity for sustainable innovation and associated HRD implications in knowledge intensive organisations, taking the perspective that social capital is a key influencing condition. Design/methodology/approach: – This qualitative case-study concerned a large-scale innovation project between knowledge-intensive organisations. Semi-structured interviews were conducted with 20 participants from six innovation groups as well as with the project management. Findings: – Findings showed that four dimensions of social capital influence knowledge productivity, each requiring a minimum quality to create a rich innovation environment for sustainable results. The relational and cognitive dimensions seem most important, while the action dimension makes them productive. Knowledge productivity appears twofold, i.e. organisational innovation, and professional ability for future innovation. Found are 18 new indicators. Research limitations/implications: – Only one large-scale inter-organisational case was conducted. Practical implications: – It is suggested that project management, group leaders and HRD officers target social capital as condition for knowledge productivity that should be stimulated, not just by planned interventions, but by "being" there as supporter, coach and mediator. Originality/value: – The article contributes to our knowledge about innovations in knowledge-rich organisations, broadens the concept of knowledge productivity, and provides a new framework of social capital as intervention model for HRD. In addition, not often dealt with in literature, the dynamic of innovation is shown.